Reposisi Hakikat Beragama di tengah Kemajemukan Indonesia - Didimus Sutanto B Prasetya; Candra Gunawan Marisi (Sekolah Tinggi Teologi Baptis, Jakarta, 2022)
The philosophy of the state of the Indonesian people is Pancasila with the first principle